Driving forces of the Canadian economy: An accounting exercise - Simona E. Cociuba; Alexander Ueberfeldt (Bank of Canada, 2008)
This paper analyses the Canadian economy for the post 1960 period. It uses an accounting procedure developed in Chari, Kehoe, and McGrattan (2006). The procedure identifies accounting factors that help align the predictions of the neoclassical growth model with macroeconomic variables observed in the data. The paper finds that total factor productivity and the consumptionleisure trade-off the productivity and labor factors are key to understanding the changes in output, labor supply and labor productivity observed in the Canadian economy. The paper performs a decomposition of the labor factor for Canada and the United States. It finds that the decline in the gender wage gap is a major driving force of the decrease in the labor market distortions. Moreover, the milder reduction in the labor market distortions observed in Canada, compared to the US, is due to a relative increase in effective labor taxes in Canada.
Keywords: E65; E24; O41; O51; 330; Labour markets; Potential output; Productivity; Produktivität; Arbeitsangebot; Gesamtwirtschaftliche Produktion; Weibliche Arbeitskräfte; Lohndifferenzierung; Kanada; USA